Implementasi Pendidikan Seksual pada Siswa SMAN 2 Karawang - Tika Aprilia; Masykur H Mansyur; Neng Ulya (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Talking about a child's education at school is the responsibility of parents, as parents need to pay attention to the provision of their first education when they were young, especially sex education for children at the age of middle age, sex education is very important to support their curiosity against the opposite sex at school. Where at their age there is a sense of liking and liking and sharing stories from one another and until finally a closeness arises between girls and boys, this needs to be owned and understood by all parents to fulfill their child's education. Sex education in schools is still a polemic at this time, there are still many parents who have taboo thoughts on sex education that tbe given to their children. Therefore, sex is naturally a task of adolescent development, it should be accompanied by the fulfillment of good sexual education. Islam considers sex as a sacred thing, the nature of every human being and even as a means of getting closer to Allah. Objectives Sexual education aims to teach about reproductive health organs, sexually transmitted diseases and HIV/AIDS, pregnancy, and contraceptives that can be used. Sexual education can also prevent acts of sexual violence, rape, sex outside of marriage, and also marriage at an early age. The method used in this research is qualitative based on data collection from books and magazines and is supported by field research to strengthen the theoretical results of existing expert opinions by linking them to practice in the field. The results obtained in this study which was carried out at SMAN 2 Karawang made many benefits, especially for teenagers and also the role of parents at home and the school to be more careful in maintaining and educating their children when entering adolescence by providing an understanding of the importance of sex education for children. himself and his future.